Induction of autophagy is essential for monocyte-macrophage differentiation - Zhang, Yan (American Society of Hematology, 2012)
Monocytes are programmed to undergo apoptosis in the absence of stimulation. Stimuli that promote monocyte-macrophage differentiation not only cause cellular changes, but also prevent the default apoptosis of monocytes. In the present study, we demonstrate that autophagy is induced when monocytes are triggered to differentiate and that the induction of autophagy is pivotal for the survival and differentiation of monocytes. We also show that inhibition of autophagy results in apoptosis of cells that are engaged in differentiation. We found that the differentiation signal releases Beclin1 from Bcl-2 by activating JNK and blocks Atg5 cleavage, both of which are critical for the induction of autophagy. Preventing autophagy induction hampers differentiation and cytokine production; therefore, autophagy is an important transition from monocyte apoptosis to differentiation.